Analysis of risk factors for prolong hospitalization in chronic subdural hematoma undergoing single burr hole and drainage (Nepal Journal of Neuroscience, 2021)
IntroductionSingle burr hole surgery for Chronic subdural hematoma (CSDH) is commonly performed neurosurgical procedure with >90% favorable outcome and less hospital stay. However, sometimes hospital stay may be prolonged due to associated prognostic factors, even in patients with favorable outcome. This study aims to analyze the early outcome of single burr hole and drainage surgery and factors that may be associated with prolong hospitalization.Materials and methodA retrospective analysis of the patients who underwent single burr hole and drainage for CSDH from sept 2017 to may 2020 in Nepal Mediciti hospital. The patients with B/L CSDH, who underwent double burr hole and drainage or craniotomy evacuation or conservatively managed patients were excluded from the study. Early outcome was assessed using Glasgow outcome score at 7 days. Effect of use of antiplatelet/ anticoagulant drugs, age, comorbidity, preoperative Glasgow coma score on number of hospital stay was analyzed. Chi-square test was used for statistical analysis in SPSS version 25.ResultsOut of 85 patients, 73 were male. Mean age was 63.8 years. Early outcome in 7 days was favorable with GOS (4-5) in 90.6%. The use of antiplatelet or anticoagulant drugs was more common amongst patients with age > 70 years (p=0.01). The number of hospital stay was associated with age (p=0.00), antiplatelet or anticoagulant drugs (p=0.00), comorbidities (p=0.001), preoperative GCS(P=0.001) and GOS at 7 days (p=0.001).ConclusionSingle burr hole and drainage surgery for CSDH mostly produce favorable outcome. The use of antiplatelet or anticoagulant drugs is more common in patients above 70 years. Age, antiplatelet or anticoagulant drugs, comorbidities, preoperative GCS, GOS at 7 days are related with longer hospital stay.